Spatiotemporal evolution and driving mechanisms of the transformation of production-living-ecological land in peri-urban areas under the construction of the Guangdong-Hong Kong-Macao greater bay area: a case study of Huiyang district, China - Xiong, Bo; Deng, Liting; Luo, Gongmei; Pan, Weihao; Lao, Xiaomin; Zhu, Zhihua; Yin, Hui (Frontiers in Environmental Science, 2026)
Against the backdrop of rapid development in the Guangdong-Hong Kong-Macao Greater Bay Area (GBA), the spatiotemporal evolution of Production-Living-Ecological Land (PLEL) in its peri-urban regions has emerged as a critical research focus for achieving regional coordinated development. This study employs Huiyang District as a representative case study area, utilizing multisource geospatial data and analytical methodologies including land use dynamic degree, land transfer matrix, binary logistic regression, and ROC analysis to systematically investigate PLEL’s spatiotemporal evolution patterns and underlying driving mechanisms from 2007 to 2023. The empirical results demonstrate that: (1) During the observation period, aggregate production and ecological land areas exhibited a declining trend, while living land manifested persistent expansion, reflecting accelerated urbanization process and intensified population concentration. Specifically, between 2007 and 2015, production and ecological land areas decreased significantly while living land expanded markedly, reflecting accelerated urbanization. From 2015 to 2023, the decline in production land substantially moderated, whereas ecological land diminution accelerated. Living land maintained a consistent expansion throughout both periods. (2) Spatial analysis revealed a stable concentric pattern emerged, characterized by living land at the urban core, encircled by production land, with ecological land occupying the peripheral zones. Notable land conversion dynamics were observed between ecological and production land, revealing the tension between conservation and development. Living land conversions to other categories remained negligible, with its expansion predominantly sourced from production land, suggesting urban expansion has largely occurred through agricultural land appropriation. (3) Driving factor analysis identified population size as the predominant influence. Following GBA development, the impact of population size on living land expansion intensified. Model validation through ROC curve analysis confirmed robust predictive performance. This research systematically elucidates PLEL’s spatiotemporal evolution patterns and driving mechanisms within a GBA peripheral urban unit, thereby contributing scientific insights for territorial spatial optimization in rapidly urbanizing regions.